Refinamento de superfícies de quadriláteros baseado em templates - Nakano, Davi Yoshinori Cangussú (Universidade Federal de São Carlos, 2013)
The computational representation of objects by means of polygonal meshes is widely used in various areas such as modeling, simulation, engineering, rendering process and various other CAD (Computer-Aided Design) and CAE (Computer-Aided Engineering) applications. These polygonal meshes are commonly built with triangles and processing these elements is widely studied, making that such techniques are well established and robust. However, there is a growing interest in quadrilateral meshes as they provide important characteristics for applications such as texturing and modeling with splines. With the increasing interest in the study of unstructured quadrilateral surfaces, there is the rise of new processing techniques related to simplification and refinement. This dissertation presents a complete pipeline for indirect generation of quadrilateral surface meshes, proposing a new refinement method of quadrilateral meshes. This new method is a local iterative subdivision process, ensuring the consistency of the mesh at each iteration and has the following main features: ability to guide the quality of generated quadrilaterals; control the number of generated elements; generate a family of models; control quadrilaterals density (adaptivity) and control the alignment of quadrilaterals lines with features lines of the model. The implementation restricts the refinement to homeomorphic models to a sphere. The results presented illustrate the effectiveness of the refinement technique and adaptivity control.
Keywords: Computação - matemática; Quadrilátero; Geometria computacional; Malhas (Matemática); Superfícies (Matemática); Templates; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO